Dampak Pelatihan Pengoperasian dan Perawatan Mesin Pencacah Sampah Plastik Bagi Komunitas Ciliwung Depok dan Warga RW 02 Pancoran Mas Depok - Adi Syuriadi; Dianta Mustofa Kamal; Ahmad Bustomi; Arifia Eka Yuliana; Andy Permana Rusdja; Muhamad Hanhan Nugraha (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2026)
The issue of biomass waste along the Ciliwung River and household waste, poses significant environmental risks. Chopper technology has emerged as a potential solution to convert plastic waste into valuable products, in this case, plastic pellets. This community service initiative aims to enhance participants' skills in operating and maintaining chopper machine, which is used to convert plastic bottle waste into plastic pellets. The training was conducted over one day with 20 participants from the Ciliwung Depok Community and residents in RW 02, Pancoran Mas District, Depok City. The activities included theoretical presentations, equipment demonstrations, hands-on practice, and evaluations through pre-tests and post-tests. Data were analyzed using the Paired Two Sample for Means method. The training demonstrated a significant improvement in participants' knowledge and skills, as evidenced by a statistically significant difference in the average scores of the pre-test and post-test (p-value < 0.05). The results indicate that the training had a substantial impact on the participants' abilities before and after the training. Similar programs are expected to be implemented in other communities to raise environmental awareness and promote the use of eco-friendly technologies.